“Corporate Efforts to Tackle Corruption: An Impossible Task?” The Contribution of Thomas Dunfee - Schwartz, Mark S. (Journal of business ethics, 2009)
Thomas W. Dunfee, in addition to his many other contributions to business ethics literature, has (along with several co-authors) generated a stream of research that attempts to tackle the issue of corruption. Dunfee’s research on corruption includes three primary contributions: (1) the introduction of “Integrative Social Contract Theory” which provides a normative theoretical framework by which to judge the morality of global business activity including corruption; (2) the “C2 Principles” (Combating Corruption), which outline specific content and implementation measures that corporations can voluntarily adopt to combat corruption; and (3) a normative evaluation of “guanxi,” a concept which can lead to questionable corruption practices in China. The article will highlight Dunfee’s contribution to the literature and suggest future research directions based on his academic work.